Influence of labelling features on purchase decisions: Exploratory study into the Generation Z beverage consumption patterns - Erik Janšto; Juraj Chebeň; Peter Šedík; Radovan Savov (Amfiteatru Economic, 2024)
The growing purchasing power and unique purchase behaviours of Generation Z have captivated the attention of academics, marketers, and researchers, who are keen to understand the nuances of this cohort's consumption patterns. While current studies focus on factors influencing consumer choices, we can hardly find studies focusing on understanding the dynamic interplay between intrinsic and extrinsic cues in influencing consumer behaviour, specifically in the context of alcoholic beverages like wine. The importance of this study lies in a deeper investigation into how these factors collectively impact consumer perceptions and decisions. This study specifically delves into the intriguing domain of their beverage consumption preferences, offering insightful revelations into their distinct buying habits and brand inclinations. The main objective of this research is to identify the influence of label characteristics on the changing buying patterns of Generation Z. Using factor analysis, multiple correspondence analysis (MCA), and Friedman's test, we have analysed the behaviour of 431 consumers from 2 EU countries. The results revealed product identity and sensory appeal as two hidden factors with a significant impact on consumer choice. In particular, sensory profiles that showcase a reputable brand and highlight distinctive grape varieties, countries of origin, and wine regions are likely to resonate with young people. Conversely, companies may be able to de-emphasise information about quality designations and awards to develop a more youth-focused strategy. Additionally, the MCA results reveal differences in the frequency and occasions of drinking across gender and place of residence groups. The further research could focus on a broader spectrum of beverage cross-generational and intercultural preferences considering psychological and social factors that influence purchasing decisions, such as peer influence, marketing campaigns, or environmental consciousness.
Keywords: M31; M37; Q13; 330; consumer choice; generation Z; iGeneration; intrinsic and extrinsic factors; labelling; product identity; purchase behaviour; sensory appeal; wine